Stability Indicating HPLC Method for the Determination of Hydrochlorothiazide in Pharmaceutical Dosage form - Sachin Bhagwate and N. J. Gaikwad (Journal of Applied Pharmaceutical Science, 2013)
A stability indicating analytical method has been developed and validated. In this study Hydrochlorothiazide was degraded under different stress test conditions as per International Conference on Harmonization. The degraded samples were used to develop a stability-indicating high performance liquid chromatographic (HPLC) method for the Hydrochlorothiazide. The Hydrochlorothiazide was well separated from degradation products using a reversed-phase (C-18) column and a mobile phase comprising of Methanol: Buffer pH- 3.2 (60:40 v/v) and other HPLC parameters were flow rate 1 mL/min, detection wavelength 270 nm and injection volume 20 µl. The method was validated for linearity, precision, accuracy, ruggedness and robustness. Results obtained after validation study indicating that the proposed single method allowed analysis of Hydrochlorothiazide in the presence of their degradation products formed under a variety of stress conditions. The developed procedure was also applicable to the determination of stability of the Hydrochlorothiazide in commercial pharmaceutical dosage form.
Keywords: Hydrochlorothiazide, HPLC, Validation, Stability, De